2018
DOI: 10.3991/ijet.v13i09.8479
|View full text |Cite
|
Sign up to set email alerts
|

Secondary School Students’ Perceptions on the Use of Google+ towards Improving ESL Writing Skills

Abstract: The use of social media in teaching has also revolutionized the way learning takes place. At higher education levels, measures have already been taken in incorporating the use of social media for learning purposes especially in the teaching of language. However, at secondary school levels, educators are still having doubts about using social media due to multiple issues. Thus, this study was conducted to investigate the perceptions of secondary school students and a teacher in Malaysia on the use of Google+ t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 10 publications
3
36
0
1
Order By: Relevance
“…So, what is lacking in this flipped learning approach is studies on the effectiveness of the approach using the right framework as well as the acceptance level in which the factors that influence the learners' choices are being discussed. Furthermore, Mohamad, Ghazali, and Hashim (2018) claimed that teachers must be aware of how to integrate technology as one of the learning tools in the teaching of English as a Second Language (ESL) (Mohamad, M., Ghazali, N., & Hashim, H., 2018). Hence, more studies on the acceptance level should be conducted using the right conceptual framework…”
Section: The Development Of Flipped Learning Approachmentioning
confidence: 99%
“…So, what is lacking in this flipped learning approach is studies on the effectiveness of the approach using the right framework as well as the acceptance level in which the factors that influence the learners' choices are being discussed. Furthermore, Mohamad, Ghazali, and Hashim (2018) claimed that teachers must be aware of how to integrate technology as one of the learning tools in the teaching of English as a Second Language (ESL) (Mohamad, M., Ghazali, N., & Hashim, H., 2018). Hence, more studies on the acceptance level should be conducted using the right conceptual framework…”
Section: The Development Of Flipped Learning Approachmentioning
confidence: 99%
“…Similarly, another researcher found that MOOC allows learners to obtain autonomy and responsibility in language learning [22]. Therefore, the ESL learner autonomy in learning the language through MOOC is an advantage that can be exploited by the institutions [23]. In addition, a study by [5] suggested that MOOC provides a learning environment with two instructors that will be helpful to the learners [24].…”
Section: Benefits Of Mooc In Esl Learningmentioning
confidence: 99%
“…However, of all language skills, writing skill has found out to be rather difficult. This statement is further supported by Mohamad, Ghazali and Hashim (2018), where they have also stated that writing skill is an essential aspect of academic performance yet it is commonly known as a difficult area for second language learners. So, how shall we classify one as a competent writer?…”
Section: Introductionmentioning
confidence: 84%